Fazer ver e fazer falar: notas sobre o estilo filosófico de Merleau-Ponty - Cardim, Leandro Neves (Discurso, 2021)
Through the investigation of these two figures of classical rhetoric in Merleau-Ponty’s work we intend to verify how he incorporates them into his philosophy. To accomplish this task the article compares passages from all periods of his work. When the philosopher uses these figures, he makes us think about the relations of painting, cinema and literature with philosophy. By working through these questions, the article aims not only to conduct a deep question about how Merleau-Ponty works with traditional issues, but also about the scope of ontology.